(untitled) (Journal of Informatics and Mathematical Sciences, 2019)
In this paper, we derive a general expression for the entries of the rth power ( rN ) of one type of the n× n complex pentadiagonal matrix for all n ≥ 4( r-1), in terms of binomial coefficients.